The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/elan.201800474
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Smartphone‐based Electrochemical Biosensing

Abstract: Point‐of‐care (PoC) biosensors offer promising solutions to today's adverse and costly healthcare issues by moving diagnostic tools closer to the patient. The ubiquity of smartphones has brought about an emergence of PoC devices, which leverage the smartphone's capabilities, enabling the creation of low‐cost and portable biosensors. Electrochemical biosensors are well suited for PoC testing since the transducers can be miniaturized and inexpensively fabricated. This review paper discusses recent developments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 102 publications
0
63
0
Order By: Relevance
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
“…[168][169][170][171][172][173][174] Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone-based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures 10 to 13). [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192] Zhao et al, 193 as shown in Figure 8A, developed a fluorescent smartphone-based label-free sensor to detect Fe (III) by employing the quenching effect. The 3D printed adapter uses a 365-nm UV LED and a smartphone camera.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%
“…In 2018, over 1.56 billion smartphones www.advmattechnol.de for detection of analytes, Sun and Hall reviewed off-phone electrochemical biosensors for POC applications. [19] However, since multiple biosensing modalities are typically coordinated together for the end user via a single smart device, there will be a need to examine different types of biosensing functions through a single lens. Also, it will be necessary to examine biosensing in combination with data processing, as it is the combination of these functions-which will feedback into the design of the biosensors-that will generate actionable insight, especially with advances in artificial intelligence (AI) and the expanding volume of health data.…”
Section: Introductionmentioning
confidence: 99%
“…Other reviews have covered biosensing modalities and applications in detail. [1,13,19,20,24,25,28,29]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation